Hubungan Kualitas Layanan Kesehatan Dengan Minat Kunjungan Ulang Pasien Rawat Jalan Di Klinik Pratama Syafana Medika - Dewi Sri Rahayu; Dwi Nur Siti Marchamah; Wahyuni Arumsari (Indonesian Journal of Health Community, 2024)
Pratama Syafana Medika Clinic has experienced an up-and-down trend in the number of outpatients over the last six months. Based on initial observations, the causes of the decrease in the number of patients include poor quality of services provided, slow treatment of patients, inadequate medical equipment, and inadequate building facilities. The type of research is quantitative analytical with a cross-sectional research design. The study population included all 3,151 patients at the Pratama Syafana Medika Clinic. Next, to determine the sample size, researchers used the Slovin formula. The sampling technique uses purposive sampling. The results of bivariate research using the chi-square test show that the relationship between the quality of health services on the dimensions of reliability is obtained at sig-p= 0.002, responsiveness is obtained at sig-p= 0.001, assurance is obtained at sig-p= 0.001, empathy is obtained ) obtained sig-p= 0.001, direct evidence (tangible) obtained sig-p= 0.000 which means there is a relationship between quality of health services on patient interest in repeat visits at Pratama Syafana Medika Clinic. Suggestions for Pratama Syafana Medika Clinic to further improve the quality of health services to increase the number of patients interested in repeat visits.